GAMBARAN PENGETAHUAN KELUARGA TENTANG EFEK SAMPING KEMOTERAPI PADA ANAK DI YAYASAN KASIH ANAK KANKER YOGYAKARTA - Fatma Laili Nugraheni; Ida Mardalena; Yustiana Olfah (Caring : Jurnal Keperawatan, 2018)
Cancer is one of the leading causes of death worldwide. Basic Health Research The Results of Basic Health Research 2013 (Riskesdas) shows the prevalence of cancer of children aged 0-14 years amountdeto 16,291 cases. While the most common type of cancer suffered by children in Indonesia is leukemia and eyeball cancer or retinoblastoma. Chemotherapy is a cancer treatment using drugs or hormones. Children who undergo chemotherapy will experience symptoms as nausea, vomiting, decreased appetite, fever and fatigue (fatigue). The purpose of this study is to determine the description of family understanding about the side effects of chemotherapy in children in Yayasan Kasih Anak Kanker Indonesia-Jogjakarta. This research uses descriptive research type with research design that is quantitative. The sampling technique used is total sampling with 45 respondents. The instrument used is questionnaire. This research was conducted from March 2017 until May 2017. It was found that some respondents had good knowledge about chemotherapy side effect that is 25 people (59,5%). Characteristics of respondents who had good knowledge are respondents whose age in the range of 36-45 years (28.6%). Respondents who had good knowledge about the side effects of chemotherapy were respondents who had a junior secondary education of 12 respondents (28.6%), with IRT work of 13 (30.9%), earning less than Rp.1.500.000 and respondents Never get information has good knowledge. The researchers concluded that some respondents had good knowledge about the side effects of chemotherapy.